Large-Scale Landslide Susceptibility Mapping Using an Integrated Machine Learning Model: A Case Study in the Lvliang Mountains of China - Xing, Yin; Yue, Jianping; Guo, Zizheng; Chen, Yang; Hu, Jia; Travé, Anna (Frontiers in Earth Science, 2021)
Integration of different model may improve the performance of landslide susceptibility assessment, but few studies have test it. The present study aims at exploring the way to integrating different models and comparing the results among integrated and individual models. Our objective is to answer this question: Will the integrated model have higher accuracy compared with individual model? The Lvliang mountains area which was a landslide prone area in China was taken as the study area, and ten factors were considered in the influencing factors system. Three basic machine learning models (the back propagation (BP), support vector machine (SVM), and random forest (RF) models) were integrated by an objective function where the weight coefficients among different models were computed by the gray wolf optimization (GWO) algorithm. 80% and 20% of the landslide data were randomly selected as the training and testing samples, respectively, and different landslide susceptibility maps were generated based on GIS platform. The results illustrated that the accuracy expressed by the area under the receiver operating characteristic curve (AUC) of the BP–SVM–RF integrated model was the highest (0.7898), which was better than that of the BP (0.6929), SVM (0.6682), RF (0.7258), BP–SVM (0.7360), BP–RF (0.7569) and SVM–RF models (0.7298). The experimental results authenticated the effectiveness of the BP–SVM–RF method, which can be a reliable model for the regional landslide susceptibility assessment of the study area. Moreover, the proposed procedure can be a good option to integrate different models for seek an “optimal” result.